Binti's R/evolutionary Cosmopolitan Ecologies. (26th March 2019) - Crowley, Dustin
Abstract : Okorafor's Binti series consistently blurs the lines between human and other-than-human, between technological and natural/spiritual, between local and global in ways that refuse to extract or abstract humans from their entanglements with environments and others, writ large and small. Set in a post–climate change Africa embroiled in regional and interstellar conflict, the narratives' cosmopolitics are unrelentingly ecological, involving nonhuman participants and embedded in material particularities that shape conflicts and relations; at the same time, the ecology is always cosmopolitan, with those nonhuman actors exercising agency within complex worlds of difference that cross over and connect cosmos, polis, and oikos. Contrary to the sometimes-utopic connotation of both cosmopolitanism and ecology, however, such difference is neither subsumed to a harmonious whole, nor held in benign relativism. Rather, Binti depicts multispecies agency that is always in dynamic tension, driving r/evolutionary growth in posthuman relations and in the genres through which we imagine them.